Effect of pre-hospital living setting on nutritional intake route upon discharge in older adults with aspiration pneumonia: a prospective cohort study - Kohei Yamaguchi; Taiju Miyagami; Ryoko Imada; Ryosuke Yanagida; Seiko Kushiro; Toru Morikawa; Kazuharu Nakagawa; Kanako Yoshimi; Toshio Naito; Haruka Tohara (BMC Geriatrics)
Abstract Background Aspiration pneumonia, which often recurs due to dysphagia, worsens as patients move between homes, facilities, and hospitals. The impact of pre-hospital living setting on oral intake at discharge remains unclear. The purpose of this study was to identify the effects of the pre-hospital living setting on the nutritional intake route upon discharge in older patients with aspiration pneumonia. Methods This prospective cohort study included patients aged ≥ 65 years who were admitted to an acute care hospital and diagnosed with aspiration pneumonia. Patients were followed up until discharge or death during hospitalisation. Patient demographic information, pre-hospital living setting (home or nursing facility), functional oral intake scale (FOIS) score, pneumonia severity index, clinical frailty scale score, history of aspiration pneumonia, and pneumonia recurrence during hospitalisation were recorded. Binary logistic regression was used to assess the impact of the pre-hospital living setting on oral intake at discharge as the primary outcome. Results Among the 89 included patients (52 males (58.4%); mean age, 84.8 ± 7.9 years), 39.3% (n = 35) had pneumonia recurrence during hospitalisation. The average follow-up period was 44.0 ± 36.6 days. The pre-hospital living setting was independently associated with the nutritional intake route upon discharge (odds ratio = 7.72, 95% confidence interval (95%CI) = 1.70–35.1, p = 0.008). Conclusions The pre-hospital living setting could serve as a good indicator of the nutritional intake route upon discharge. It is essential to optimize care in both nursing facilities and hospital settings when caring for older patients with aspiration pneumonia.